2008
DOI: 10.2105/ajph.2007.119826
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Among Adults Who Experienced Maltreatment During Childhood

Abstract: Persons who experienced childhood maltreatment had significant and sustained losses in health-related quality of life in adulthood relative to persons who did not experience maltreatment. These data are useful for assessing the cost-effectiveness of interventions designed to prevent child maltreatment in terms of cost per quality-adjusted life years saved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(182 citation statements)
references
References 57 publications
9
162
1
5
Order By: Relevance
“…International research groups have found relationships between childhood adversity and later depression, anxiety, posttraumatic stress disorder (PTSD), eating disorders, sleep disorders, substance abuse, behavioral disorders, suicide ideation, and self-harm (34)(35)(36)(37)(38)(39). These results are shown to be strong and robust, and have been confirmed by systematic reviews and meta-analyses that included several million participants across different world regions (40)(41)(42).…”
Section: Childhood Adversity and Psychopathologymentioning
confidence: 84%
See 2 more Smart Citations
“…International research groups have found relationships between childhood adversity and later depression, anxiety, posttraumatic stress disorder (PTSD), eating disorders, sleep disorders, substance abuse, behavioral disorders, suicide ideation, and self-harm (34)(35)(36)(37)(38)(39). These results are shown to be strong and robust, and have been confirmed by systematic reviews and meta-analyses that included several million participants across different world regions (40)(41)(42).…”
Section: Childhood Adversity and Psychopathologymentioning
confidence: 84%
“…Based on the literature review of childhood maltreatment and psychiatric disorders (34)(35)(36)39), it was expected that differences in the prevalence of some psychiatric disorders, such as a higher prevalence of depression, anxiety, and CD among maltreated adolescents would be found in these youths. However, some of the results were unexpected.…”
Section: Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Early childhood experiences and perceptions of adversity and maltreatment influence pyschological and physiological responses [35][36][37]. Sustained experiences not buffered by supportive relationships or in the absence of protective relationships create prolonged activation of the stress response and result in long term behavioral (depression, dysfunctional coping activities) and health consequences (elevated blood pressure,glucose, cortisol, inflammation).…”
Section: Introductionmentioning
confidence: 99%
“…Children who experience abuse or neglect are at high risk for developing long-term emotional, physical, and medical problems related to their early traumatic experiences [2,3]. Studies on CAN recidivism indicate that maltreated children are six times more likely to experience recurrent maltreatment than children who have never been abused [4].…”
mentioning
confidence: 99%